2006
DOI: 10.1007/s11906-006-0031-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of community programs in controlling blood pressure

Abstract: Despite more than 30 years of intense activity to improve control--and more recently prevention--high blood pressure continues to be a major public health problem. Evidence-based reviews have identified best practices and quality improvement strategies to address prevention and control. Since the 1970s, community-based programs have been instrumental in raising awareness, increasing knowledge, and promoting changes in health behavior to improve blood pressure control. Most of these programs have emphasized the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…2,5 Based on this information, it can be concluded that, if sustained, the observed BP reductions in KOT would lead to healthier aging. The KOT model shares components of other community-based interventions for BP lowering, 11,[13][14][15][16][17][18][19][20][21]24 although the central involvement of peer volunteers is novel. The majority of programs using lay health volunteers for BP control are educationally focused, 16,24 and those that venture into the realm of monitoring, tracking, and referral often directly involve the use of health profes-sionalsFphysicians, pharmacists, nurses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,5 Based on this information, it can be concluded that, if sustained, the observed BP reductions in KOT would lead to healthier aging. The KOT model shares components of other community-based interventions for BP lowering, 11,[13][14][15][16][17][18][19][20][21]24 although the central involvement of peer volunteers is novel. The majority of programs using lay health volunteers for BP control are educationally focused, 16,24 and those that venture into the realm of monitoring, tracking, and referral often directly involve the use of health profes-sionalsFphysicians, pharmacists, nurses.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 That is, BP control depends upon a number of interrelated environmental and individual factors such that efforts focused on individual contacts have limited capacity to reach entire populations. 1,11 Recognizing this, Healthy People 2010 has identified the community as a critical partner in efforts to improve chronic disease-related health outcomes. 12 A number of community models to address BP control have been advanced in the literature.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…
There are currently lifestyle modifications and medications that are highly successful in controlling hypertension. Nevertheless, many hypertensive individuals do not implement lifestyle changes and fail to adhere to medication regimens (Fullwood et al, 2006;Wetzels et al, 2006). The current study sought to understand both sociodemographic and intrinsic factors associated with the implementation of recommended lifestyle modifications for treatment of hypertension.
…”
mentioning
confidence: 99%